2009
DOI: 10.1016/j.aquaculture.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of fish meal with plant protein sources and energy budget for white shrimp Litopenaeus vannamei (Boone, 1931)

Abstract: Fish meal (FM) has long been considered an essential ingredient for the formulation of shrimp feeds. Until recently, 12%FM was considered a minimum amount, below which weight gain would become reduced due to a reduction in feed intake. In order to test this perceived minimum value, an experiment was conducted on a long-term basis with 4 replicates. Four practical isonitrogenous and isoenergetic diets were formulated for Litopenaeus vannamei juveniles. Survival, weight gain, feed conversion ratio (FCR) and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
124
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 39 publications
19
124
2
5
Order By: Relevance
“…The observation for growth performance also showed that up to 33% of the FM in a practical diet for whiteleg shrimp, reared in biofloc system, could be effectively substituted by the soybean meal (SBM). Previously, numerous studies have been conducted to evaluate the suitability of various feed ingredients as alternative protein sources for FM; as partial or even total replacement of FM by plant ingredients in the diet of L. vannamei has been reported by several authors (Amaya et al 2007;Suárez et al 2009;Olmos et al 2011;Ye et al 2011;Liu et al 2012;Yue et al 2012;Gu et al 2013;Sá et al 2013;Sookying et al 2013;Kuhn et al 2016;Xie et al 2016). In the present study, application of methionine and lysine in the diet did not significantly influence the growth performance.…”
Section: Discussionsupporting
confidence: 52%
“…The observation for growth performance also showed that up to 33% of the FM in a practical diet for whiteleg shrimp, reared in biofloc system, could be effectively substituted by the soybean meal (SBM). Previously, numerous studies have been conducted to evaluate the suitability of various feed ingredients as alternative protein sources for FM; as partial or even total replacement of FM by plant ingredients in the diet of L. vannamei has been reported by several authors (Amaya et al 2007;Suárez et al 2009;Olmos et al 2011;Ye et al 2011;Liu et al 2012;Yue et al 2012;Gu et al 2013;Sá et al 2013;Sookying et al 2013;Kuhn et al 2016;Xie et al 2016). In the present study, application of methionine and lysine in the diet did not significantly influence the growth performance.…”
Section: Discussionsupporting
confidence: 52%
“…Marine shrimp feeds are still dependent on different degrees of fishmeal, due to its attractability and palatability proprieties and nutritional content, including amino acids and essential fatty acids, as well as vitamins and minerals (Amaya et al, 2007a,b;Suárez et al, 2009). However, a reduction or replacement of fishmeal for a suitable alternative ingredient would be desirable, preferably one that is cheaper and renewable.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group developed a program of experiments on shrimp nutrition that successfully tested plant meal such as plant protein concentrates as fishmeal substitutes (Maldonado, Cuzon, Guzmán, Brito, Soto, Arena, & Gaxiola, 2009;Suárez, Gaxiola, Mendoza, Cadavid, Garcia, Alanis, Suárez, Faillace, & Cuzon, 2009;Maldonado, Guillen, Pantoja, Arena, Ezquerra-Bauer, Alvarez-González, Cuzon, & Gaxiola, 2012;Suarez, Gaxiola, Posso, Garcia, Alanis, Suárez, Faillace, & Cuzon, 2012). However, plant protein sources have limitations related to decreased feed intake due to lack of appetability for shrimp, and by the presence of phytate, an antinutritional factor (AF), which limits bioavailability of phosphorus and other minerals (Lee and Meyers, 1996;Mendoza, Aguilera, & Montemayor, 2000).…”
Section: Introductionmentioning
confidence: 99%